h+-65=27

Simple and best practice solution for h+-65=27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for h+-65=27 equation:



h+-65=27
We move all terms to the left:
h+-65-(27)=0
determiningTheFunctionDomain h-65-27+=0
We add all the numbers together, and all the variables
h=0

See similar equations:

| 2x+13=-3+53 | | 11v=14+4v | | 7x−4=20+3x | | 14+3n=8n-39n-4) | | v−87=-74 | | 7^(2x-5)=43 | | v+24=71 | | (4x+18)+(8x-14)=180 | | y+-77=-66 | | 4x-12=12x-4 | | 54-v=242 | | m−45=7 | | y+-2=-100 | | 12s/4=30 | | j+-6=-2 | | 6a-8-3a=4 | | x^2+5x=21+12x | | 1/2x-3x=5x | | 3.7+6x=52.9 | | 8z-2=-17 | | 5+5s=9s+2 | | ⅔n-6=18 | | 5x=15/17 | | -5(x-3)-2x=46-4(x-1 | | 4^2x+1=33 | | |z-9|+6=8 | | -9×-y=-27 | | -7k-8(-8k-2)=-4K-45 | | 79x+50=98 | | 3x+25+x-20+x=180 | | 180=2x-56 | | -30x^2-10x+0=0 |

Equations solver categories